School Management Tips In Excaving Education Funding Sources (Arfannur: Journal of Islamic Education, 2024)
This research aims to identify potential sources of education funding and find out about school management tips in exploring sources of education funding. This research is a type of library research, which is research whose object of study uses library data in the form of books as the source of data. The results of the study show that the excavation of educational funding sources in schools and madrasas involves various sources, including budgets from the central and regional governments. Contributions from foundations, donations from students' parents, school committees, alumni, and foster parents are also important. Alternative fundraising such as charity Jariyah, zakat mal, and non-governmental donations help improve the quality of education. The management of education funds requires an effective strategy and transparency. Management tips that can be done are that the use of the budget must be precise, efficient, and transparent, as well as strict monitoring of expenditures. Accountable and transparent management of education funds is very important to support the progress of education and improve the quality of services provided to students.